2020
DOI: 10.1101/2020.11.19.390419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Beta- And Gamma-Synucleins Modulate Synaptic Vesicle-Binding of Alpha-Synuclein

Abstract: SUMMARYα-Synuclein (αSyn), β-synuclein (βSyn), and γ-synuclein (γSyn) are abundantly expressed in the vertebrate nervous system. αSyn functions in neurotransmitter release via binding to and clustering synaptic vesicles and chaperoning of SNARE-complex assembly. The functions of βSyn and γSyn are unknown. Functional redundancy of the three synucleins and mutual compensation when one synuclein is deleted have been proposed, but with conflicting evidence. Here, we demonstrate that βSyn and γSyn have a reduced af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 86 publications
(156 reference statements)
0
6
0
Order By: Relevance
“…Indeed, our data suggest that β-synuclein, via interaction with a number of vesicular and cytosolic proteins, can potentiate formation of various molecular complexes on the surface of synaptic vesicles. This is similar to α-synuclein, which is known to interact with a variety of proteins and function as a chaperone or scaffold for the assembly of multiprotein complexes on the surface of synaptic vesicles, implicating α-synuclein in a number of molecular processes at several stages of the synaptic vesicle cycle ( 45 , 46 , 47 , 48 ). However, potentiation of vesicular uptake is not included in the list of possible functions of α-synuclein or γ-synuclein, and therefore, they are unable to compensate for the loss of this particular function of β-synuclein.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Indeed, our data suggest that β-synuclein, via interaction with a number of vesicular and cytosolic proteins, can potentiate formation of various molecular complexes on the surface of synaptic vesicles. This is similar to α-synuclein, which is known to interact with a variety of proteins and function as a chaperone or scaffold for the assembly of multiprotein complexes on the surface of synaptic vesicles, implicating α-synuclein in a number of molecular processes at several stages of the synaptic vesicle cycle ( 45 , 46 , 47 , 48 ). However, potentiation of vesicular uptake is not included in the list of possible functions of α-synuclein or γ-synuclein, and therefore, they are unable to compensate for the loss of this particular function of β-synuclein.…”
Section: Resultsmentioning
confidence: 91%
“…All three members of the synuclein family can interact with phospholipids at the outer surface of synaptic vesicles via their conserved N-terminal repeat domain, but the number of functional multiprotein complexes each member can form on a given vesicle is limited. Moreover, results of the recent study ( 48 ) suggested that synucleins modulate each other's binding to synaptic vesicle–like membranes possibly via formation of heteromeric complexes. Such synuclein complexes attract different combination of other proteins than single synuclein-based complexes ( e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Lipid binding of the synucleins reflects functional compensation, whereby in the presence of αS, the membrane association of βS and γS was enhanced. Concomitantly, the presence of βS and γS attenuated the membrane association of αS [ 54 ]. Taken together, these studies suggest that lipid binding is an evolutionary conserved biological role of βS.…”
Section: The Function Of β-Synucleinmentioning
confidence: 99%
“…Synucleins are important for the synaptic transmission and circulation of synaptic vesicles [ 22 , 23 , 24 , 25 , 26 , 27 ]. Alpha-synuclein modulates the release of neurotransmitters from presynaptic terminals by binding and clustering synaptic vesicles and chaperoning the soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) complex assembly by binding to the protein synaptobrevin-2 (VAMP2) [ 28 , 29 ] whereas beta-synuclein and gamma-synuclein modulate the synaptic vesicular binding of alpha-synuclein and thus reduce the synaptic physiological activity of alpha-synuclein [ 30 , 31 ] ( Table 1 ). Moreover, in vitro and in vivo experiments have revealed that all three members of the synuclein family have chaperone activity [ 32 , 33 , 34 ].…”
Section: Synuclein Structure and Functionsmentioning
confidence: 99%
“…Alpha-, beta-, and gamma-synucleins can bind to the dopamine transporter (DAT) and modulate its delivery to the synaptic membrane, thereby affecting dopamine neurotransmitter reuptake [ 11 , 31 , 35 ]. In turn, it has been shown through protein–protein interactions that alpha-synuclein can affect DAT activity and this effect is regulated by the gamma-synuclein concentration [ 36 , 37 , 38 ].…”
Section: Synuclein Structure and Functionsmentioning
confidence: 99%